2022
DOI: 10.20945/2359-3997000000471
|View full text |Cite
|
Sign up to set email alerts
|

Association of methylenetetrahydrofolate reductase ( MTHFR ) gene polymorphisms (C677T and A1298C) with thyroid dysfunction: A meta-analysis and trial sequential analysis

Abstract: Rui Yang and Danhua Pu were the principal investigators of this study, who were responsible for data collection, analysis and the writing of the manuscript. Rongrong Tan helped in analysis and the revising of the manuscript. Jie Wu developed the hypothesis and study design and supervised this study. All authors approved the final paper for submission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Because methyltransferases rely on the biochemical integrity of methylation reactions in the body to transfer a single-carbon unit, the completeness of that conversion will be determined by an individual’s gene variants related to that enzyme. Methylation inefficiencies due to single nucleotide polymorphisms (SNPs) in methylation-related enzymes like 5,10-methylenetetrahydrofolate reductase (C677T) are clinically relevant in various disease states [ 202 , 203 , 204 , 205 ]. Unfortunately, SNPs specifically related to the ASMT enzyme have not been extensively explored in humans but would be an excellent area for translational research that could encompass clinical identification of SNPs along with nutrient modifications for therapeutic intervention [ 206 ].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…Because methyltransferases rely on the biochemical integrity of methylation reactions in the body to transfer a single-carbon unit, the completeness of that conversion will be determined by an individual’s gene variants related to that enzyme. Methylation inefficiencies due to single nucleotide polymorphisms (SNPs) in methylation-related enzymes like 5,10-methylenetetrahydrofolate reductase (C677T) are clinically relevant in various disease states [ 202 , 203 , 204 , 205 ]. Unfortunately, SNPs specifically related to the ASMT enzyme have not been extensively explored in humans but would be an excellent area for translational research that could encompass clinical identification of SNPs along with nutrient modifications for therapeutic intervention [ 206 ].…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…Various comorbidities like intellectual disability, congenital heart defects (CHD), gastrointestinal disorders, celiac disease, thyroid disease, and otitis media occur commonly in DS patients. A metaanalysis of 817 patients and 566 controls found that MTHFR C677T is a risk factor for hypothyroidism (Yang et al 2022). Similarly, it has been found that MTHFR A1298C and MTHFR C677T are associated with the risk of CHD (Zidan et al 2013).…”
mentioning
confidence: 99%
“…Various comorbidities like intellectual disability, congenital heart defects (CHD), gastrointestinal disorders, celiac disease, thyroid disease, and otitis media occur commonly in DS patients. A metaanalysis of 817 patients and 566 controls found that MTHFR C677T is a risk factor for hypothyroidism (Yang et al 2022). Similarly, it has been found that MTHFR A1298C and MTHFR C677T are associated with the risk of CHD (Zidan et al 2013).Studies on MTHFR polymorphism in individuals with Down syndrome are lacking, though there are multiple studies on MTHFR polymorphisms as a maternal risk factor for DS (Kedar et al 2019;Brandalize et al 2009;Meguid et al 2008).…”
mentioning
confidence: 99%
“…During canine hypothyroidism, as in humans, the concentration of Hcy was negatively correlated with the concentration of total thyroxine (TT4) [ 42 , 44 , 45 ]. It is partially explained by the positive correlation between thyroid hormone levels and the activity of methylenetetrahydrofolate reductase (MTHFR), which is involved in the (re)methylation of Hcy to methionine [ 46 , 47 , 48 , 49 ]. This relationship indicates a likely role of thyroid gland disorders in developing homocysteine-dependent pathologies [ 44 , 50 ].…”
Section: Homocysteine In Pets and Farm Animalsmentioning
confidence: 99%